2004
DOI: 10.1016/j.physa.2004.06.079
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy as an exit mechanism for systems with a variable number of components

Abstract: Dynamical systems with components whose sizes evolve according to multiplicative stochastic rules have been recently combined with entry and exit processes. We show that the assumptions usually made in modeling exits are at odds with the available evidence. We discuss a recently proposed macroeconomic model with random multiplicative shocks and a mechanism for exit based on bankruptcy, which displays several observed stylized facts for firms' dynamics, like power law distributions for firms' sizes and Laplace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Lighter gray lines correspond to higher values of the parameter. (footnote continued) that the simulated distribution is better approximated by a log-normal, diverging in this respect from the evidence provided by Di Delli Gatti et al (2004). 44 Admittedly, several other parameters are likely to exert an impact, such as the rate of taxation, the threshold employed in workers reservation wage function, or households' propensities to consume.…”
Section: Robustness Checksmentioning
confidence: 93%
See 1 more Smart Citation
“…Lighter gray lines correspond to higher values of the parameter. (footnote continued) that the simulated distribution is better approximated by a log-normal, diverging in this respect from the evidence provided by Di Delli Gatti et al (2004). 44 Admittedly, several other parameters are likely to exert an impact, such as the rate of taxation, the threshold employed in workers reservation wage function, or households' propensities to consume.…”
Section: Robustness Checksmentioning
confidence: 93%
“…41 We obtain p-value ¼0, χ 2 ¼ 26.074 for credit degree distribution, and p-value ¼0, χ 2 ¼ 77.912 for banks' credit distribution. 42 In particular, Di Delli Gatti et al (2004) suggest that both distributions have right tails scaling down to a Pareto. 43 The skewness is equal to 2.16 for firms' bad debt and 1.97 for firms' bankruptcies, whereas the former has an excess kurtosis equal to 2.16 and the latter 1.32.…”
Section: Micro-stylized Factsmentioning
confidence: 99%
“…We choose a power law distribution for the firm's fragility indices p i because most of the measures of company performance, both positive (Axtell 2001) and negative (Fujiwara 2004, Delli Gatti et al 2004, have been found to display such power law distributions.…”
mentioning
confidence: 99%
“…if the individual price falls below a critical threshold. The probability of bankruptcy turns out to be an increasing function of the interest rate and the capital stock, and a decreasing function of the equity base inherited from the past [8,12].…”
mentioning
confidence: 99%